Predicting the spread of contamination in water distribution networks laid on sloping terrains - Jamil R.; Abdul Aziz H.; Murshed M.F. (Kuwait Journal of Science)
Contamination in domestic and drinking water during the conveyance process is one of the biggest health risks of all time. This is a very common hazard that is expected in the areas where water, sewer, and drainage pipes are laid in trenches near each other. The extent of the contamination spread in the case of intrusion through a pipe leak for water distribution networks (WDNs) laid on sloping terrain is not known. This article deals with the simulation and hydraulic analysis of organic contaminant intrusion in WDNs with significant consideration of the slope of the laid pipes. The source of organic contamination is considered to be the nearby leaking sewer water. The effects of sloping terrain on contaminant spread in the pipe network are studied in detail by injecting contaminant concentrations at eight different critical locations in the network. The results of contamination spread after a particular time at all nodes are compiled, and by using statistical techniques, a relation between the contaminant spread and pipe slope is proposed. The presented model is validated by comparing the actual values of the contaminant in water samples obtained at the site with the calculated ones, and it shows that the values deviate within the range of ±2% only, which is considered a good match. The research proves to be beneficial for the management of water distribution through pipe networks against contaminants to maintaining water quality and public health. © 2024 The Author(s)